Analytical Approach for Evaluation of Lithium‐Ion Battery Cells. Issue 12 (5th September 2016) - Wagner, Sebastian; Oberland, Alexander; Turek, Thomas
Abstract: A new method for evaluation of battery cells containing porous thin‐layer electrodes is developed. For this purpose, a typical concept of chemical reaction engineering to classify reactors by dimensionless characteristic values is used. Therefore, the system of equations describing the porous electrodes in a battery cell is transferred to dimensionless notation and corresponding dimensionless properties are developed. The required kinetic data are measured with the help of electrochemical test cells. A complete set of parameters for the description of the lithium‐ion battery is determined and the characteristic properties for the chosen example are calculated and analyzed. Finally, the performance of the anode and cathode using lithium manganese oxide and surface‐modified graphite as active materials is compared with the aid of the newly developed dimensionless parameters. Abstract : Beware of the reactor ! A new method for evaluation of battery cells containing porous thin‐layer electrodes is developed. For this purpose, a typical concept of chemical reaction engineering to classify reactors by dimensionless characteristic values is used. A complete set of parameters for the description of the lithium‐ion battery is determined and the characteristic properties for the chosen example are calculated and analyzed.